KEHIDUPAN SOSIAL EKONOMI PETANI BENGKOANG DI KECAMATAN KURANJI PADANG 1990-2012 - Ulfa, Eliza - (Pendidikan Sejarah, 2014)
Â This thesis diSCIsses about the life of bcngkoang farmers in district Kur.u1ji Padang, since 1990until 2012. The fonnulation of the problem in thi study !IS follows :economic life atler lhe bcn&koo.ns farming. how the influen<..